P-17 Advance care planning in dementia – training needs analysis for effective facilitation. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Dening, Karen Harrison; Scates, Caroline
Abstract : Advance care planning (ACP) is a voluntary process of discussion and review to help an individual who has capacity to anticipate how their condition may affect them in the future. Dementia is a progressive and life limiting illness (Sampson & Harrison Dening, 2013), where the mental capacity to make decisions can be lost fairly early on in the illness. There is a small, growing literature on ACP and its application in dementia in the UK highlighting that its uptake is small and patchy due to several factors. People with a life-limiting illness, especially dementia, are not routinely consulted about their wishes and preferences for future care. There are several potential barriers that may contribute to this in the general population, such as, procrastination, or waiting to do it later, dependence on family for decision making. However, in dementia, there are several additional barriers to initiating ACP one of which is a reluctance on the part of professionals to undertake such difficult initial conversations. This is in part due to the perception that they lack the knowledge, skills and experience to do so (Harrison Dening, Jones & Sampson, 2011). Admiral Nurses (AN) are expert practitioners in the case management of families affected by dementia. A growing aspect of their role is in supporting ACP. However, as more and more are recruited Dementia UK wanted to ensure there was a consistency across the workforce in their ability to facilitate the effective initiation and development of ACP. This paper discusses a UK-wide training needs analysis of ANs undertaken during master classes on palliative and end of life care in dementia. It will discuss results and the development of an educational intervention to equip ANs in this activity.